The reality of female Islamic studies teachers promoting values of volunteer work among female secondary school students in Makkah - Akram, Hoba Ahmed; Almontashri, Reem Mohammed (Journal of Educational and Psychological Sciences, 2024)
The study aimed to investigate the reality of promoting Islamic studies through female teachers’ promotion of volunteer work values among female secondary school students in Makkah A descriptive method was adopted, with a sample of 101 female Islamic studies teachers from secondary schools in Makkah selected randomly. A questionnaire was used as a tool to collect data after ensuring its validity and reliability, consisting of 10 items. The study found that the level of promotion of volunteer work values by female Islamic studies teachers was high, with a mean of 3.49, This can be attributed to the interest of female Islamic studies teachers in deepening the concept of volunteer work and promoting female students’ self-initiative to help others. In addition, the study found that the degree of promotion of Islamic studies by female teachers for values of solidarity and cooperation was high, with a mean of 4.04 , This is attributed to the interest of female Islamic studies teachers in deepening the concept of solidarity and cooperation values among female students through various methods, activities, and strategies that develop these aspects. Based on the results of the study, several recommendations were presented. The most important are: encouraging female students to engage in volunteer work and all associated values; developing a sense of teamwork through activating teaching strategies to promote a culture of volunteer work among female students; and the necessity of including activities in the school curriculum that focus on volunteer work concepts.